2000
DOI: 10.1046/j.1432-1327.2000.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes released during reticulocyte maturation bind to fibronectin via integrin α4β1

Abstract: Exosomes are vesicles formed in the endosomal compartment and released in the extracellular medium during reticulocyte maturation into erythrocytes. They have a clearing function because of their enrichment with some proteins known to decrease or disappear from the cell surface during maturation, e.g. acetylcholinesterase and transferrin receptor. We show here that integrin a4b1, present on the surface of erythroid precursors but absent from the mature red cell membrane, is at least partly cleared from the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(120 citation statements)
references
References 39 publications
5
112
0
1
Order By: Relevance
“…18 The recovery of exosomes from the plasma of inoculated mice was carried out in a similar way except that samples were fivefold diluted before starting centrifugations. The amounts of recovered exosomes were evaluated by measuring the activity of acetylcholinesterase (AchE), ie, a classical exosome marker, 19 through the use of the Amplex Red kit (Molecular Probes, Thermo Fisher) following the manufacturer's recommendations. The AchE activity was measured in mU/mL, where 1 mU is defined as the amount of enzyme which hydrolyzes 1 pmole of acetylcholine to choline and acetate per minute at pH 8.0 at 37°C.…”
Section: Exosome Isolation Detection and Characterizationmentioning
confidence: 99%
“…18 The recovery of exosomes from the plasma of inoculated mice was carried out in a similar way except that samples were fivefold diluted before starting centrifugations. The amounts of recovered exosomes were evaluated by measuring the activity of acetylcholinesterase (AchE), ie, a classical exosome marker, 19 through the use of the Amplex Red kit (Molecular Probes, Thermo Fisher) following the manufacturer's recommendations. The AchE activity was measured in mU/mL, where 1 mU is defined as the amount of enzyme which hydrolyzes 1 pmole of acetylcholine to choline and acetate per minute at pH 8.0 at 37°C.…”
Section: Exosome Isolation Detection and Characterizationmentioning
confidence: 99%
“…While cellular and molecular mechanisms for uptake of exosomes are yet to be comprehended, several mechanisms have been proposed (Clayton et al, 2004;Miyanishi et al, 2007;Nolte-'t Hoen et al, 2009;Rieu et al, 2000;Segura et al, 2007). First, exosomes can be taken up by phagocytosis or pinocytosis.…”
Section: Uptake Of Exosomesmentioning
confidence: 99%
“…In seminal work by Rieu et al, it was shown that integrin α 4 β 1 is present on the surface of young reticulocytes and its surface levels decrease during maturation. 134 The adhesion molecules of mature reticulocytes were detected in the exosomal fraction, suggesting that the cells use exosomes to dispose of integrins. Functional examination of the exosomes showed that α 4 β 1 integrin mediated binding of the exosomes to fibronectin.…”
Section: Adhesion Moleculesmentioning
confidence: 99%